THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP EDUCATION PROGRAM AND STUDENTS’ ENTREPRENEURIAL ORIENTATION; A CONCEPTUAL FRAMEWORK - Shukurat Moronke Bello; Muazu Hassan Muazu; Rabiu Hassan; Muhammad Yadudu; Muhammad Baffa Sani; Maryam Abubakar Koko (Universitas Pakuan, 2022)
ABSTRACTThis study aims to study further by introducing a new variable (simulation technology) in the form of game-based learning on several existing models in the hope of increasing the effectiveness of the Entrepreneurship Education Program (EEP) in fostering university students. This study adopted a survey research design, using a collection method approach for data collection and analysis. Both students and the Director of the Center for Entrepreneurship Development have targeted respondents. The data collection instruments were questionnaires and interviews. Partial Least Square and NVIVO will be used for data analysis. The results of our analysis show that the entrepreneurial learning approach used in Europe, America, and Asia, and most of the findings show a positive variation in entrepreneurial orientation. This research will revive entrepreneurial learning by enhancing the EEP curriculum and teaching pedagogy to encourage entrepreneurial orientation aimed at creating new ventures, a decent work environment, and overall productivity.ABSTRAKPenelitian ini bertujuan untuk mengkaji lebih lanjut dengan memperkenalkan variabel baru (teknologi simulasi) berupa game-based learning pada beberapa model yang ada dengan harapan dapat meningkatkan efektifitas Entrepreneurship Education Program (EEP) dalam pembinaan mahasiswa. Penelitian ini mengadopsi desain penelitian survei, dengan menggunakan pendekatan metode pengumpulan untuk pengumpulan dan analisis data. Baik mahasiswa maupun Direktur Pusat Pengembangan Kewirausahaan telah membidik responden. Instrumen pengumpulan data adalah angket dan wawancara. Partial Least Square dan NVIVO akan digunakan untuk analisis data. Hasil analisis kami menunjukkan bahwa pendekatan pembelajaran kewirausahaan yang digunakan di Eropa, Amerika, Asia, dan sebagian besar temuan menunjukkan variasi positif dalam orientasi kewirausahaan. Penelitian ini akan menghidupkan kembali pembelajaran kewirausahaan dengan meningkatkan kurikulum EEP dan pengajaran pedagogi untuk mendorong orientasi kewirausahaan yang bertujuan untuk menciptakan usaha baru, lingkungan kerja yang layak, dan produktivitas secara keseluruhan.